New Social Movements: Telaah Pustaka atas Pergeseran Paradigma dari Ideologi Menuju Identitas - Yudaningsih Yudaningsih; Yusuf Wibisono; Asep Muhyiddin (FASTABIQ: JURNAL STUDI ISLAM, 2025)
This article aims to critically examine the theoretical contribution and contemporary relevance of the work of Larana and colleagues to the study of social movements. It provides a scholarly review of the seminal book New Social Movements: From Ideology to Identity by Enrique Larana, Hank Johnston, and Joseph R. Gusfield (1994), which marked a major paradigm shift in modern social movement theory from ideology-based struggles to identity politics. The book argues that new social movements are concerned not only with the redistribution of resources but also with the recognition of identities and humanitarian values. Drawing upon cultural sociology and symbolic interactionism, Larana and his colleagues explain how collective identity is constructed as a source of solidarity, meaning, and moral legitimacy in collective action. Using a qualitative hermeneutic literature review approach, this article discusses the book’s theoretical contributions, conceptual elaborations, and empirical reflections, as well as its relevance to the study of identity politics, religious social movements, and ecological activism in the digital and global era. The study finds that collective identity remains at the core of contemporary social movement mobilization; however, the dynamics of twenty-first-century movements reveal a hybridization of the politics of meaning, political opportunities, and digital networks. Therefore, the New Social Movements paradigm remains relevant for explaining the formation of moral solidarity and collective identity, although it needs to be complemented by perspectives on globalization, digital technology, and power structures in order to provide a more comprehensive understanding of contemporary social movements.